Dynamic Behavior of a SCARA Robot by using N-E Method for a Straight Line and Simulation of Motion by using Solidworks and Verification by Matlab/Simulink - Fernini Brahim; Mustapha Temmar (Institute of Advanced Engineering and Science, 2014)
SCARA (Selective Compliant Assembly Robot Arm) robot of serial architecture is widely used in assembly operations and operations